(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In connection with the development of the professional thinking of future teachers, it is recommended that the teacher use the above communication methods in a harmonious manner. Because, if the mastery of educational tasks is based on rigor, interpersonal communication is organized on the basis of a personal-humanistic approach, and a liberal style is used, creating conditions for students’ independence and free thinking leads to an increase in positive achievements.